2018
DOI: 10.1111/cfs.12603
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with parental substance use disorder: The struggle with complex emotions, regulation of contact, and lack of professional support

Abstract: The aim of the study was to explore young people's perceptions and reflections about growing up with parents who have substance use disorder (SUD). In qualitative interviews with 12 young people (aged 13–26) and in an interpretative phenomenological analysis, we investigated their experiences of everyday life, of the relationships with the parents with SUD, and of conversations about this, both retrospectively and at the present. The findings indicated that the relationships with the parents largely occupied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
6
23
0
Order By: Relevance
“…Hardship associated with loss of, or separation from, a healthy parent, compassion with the ill parent and fear of being abandoned have previously been reported (27–29). These and other related challenges described by the children in the present study have been found in research with children from similar parental illness groups as in our study (62, 63, 65, 66). Some children were exhausted by such disturbing thoughts, others could not sleep or concentrate, while others felt overstretched or in a terrible mood (64).…”
Section: Discussionsupporting
confidence: 81%
“…Hardship associated with loss of, or separation from, a healthy parent, compassion with the ill parent and fear of being abandoned have previously been reported (27–29). These and other related challenges described by the children in the present study have been found in research with children from similar parental illness groups as in our study (62, 63, 65, 66). Some children were exhausted by such disturbing thoughts, others could not sleep or concentrate, while others felt overstretched or in a terrible mood (64).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, many young adults find it difficult to be emotionally independent from their parent who has a mental illness or substance use problem. Drawn from interviews with 12 young people aged 13–26 whose parents had substance use problems, Wangensteen et al (23) described their struggle in balancing emotional closeness and distance with their parent. In particular, those aged 18–26 felt sorry for their parent and described a sense of obligation toward them and the subsequent struggle to separate themselves emotionally when they moved out of home.…”
Section: Mechanisms Of Risk Related To Mental Health Among Young Adultsmentioning
confidence: 99%
“…Studies related to Nordic welfare-state contexts and treatment settings have found similar situations, with those children growing up with parental substance-use problems struggling in everyday life and lacking informal and professional support networks to address their needs (Itäpuisto, 2014;Ruud et al, 2015;Wangensteen, Bramness, & Halsa, 2018;Werner & Malterud, 2016).…”
mentioning
confidence: 99%
“…I would like to quote one of the male informants in the study of Wangensteen et al (2018), who is now 21 years old but has a background of living with parental substance-use problems:…”
mentioning
confidence: 99%
See 1 more Smart Citation